GENDER INEQUALITY AND WOMEN REPRESENTATION IN EXECUTIVE AND LEGISLATIVE SEATS IN NIGERIA’S FOURTH REPUBLIC: A STUDY OF LAGOS STATE (2012-2023) - OLAYINKA BABATUNDE ADEBOGUN; OPEYEMI BOYO ORITSEJOLOMI; ODUNTAN JOSEPH OLATUNJI; OLUWATUNMISE DARAMOLA (International Studies Journal)
Women make slightly more than half of Lagos state population and play a crucial role in advancing the country’s political system and democratization. However, several studies such as Onyebuchi (2022) and Atajiri (2022) have examined the political representation and the level of involvement of women in politics in Nigeria, however, they did not sufficiently define the forms and effects of gender inequality and the inadequacy inherent in women’s representation in Lagos state and implications of this on democratic values and processes in Nigeria. The research aimed at taking a new perspective at examining the phenomena and filing the gap in literature by providing a detailed analysis on the cause and effects of gender inequality and women political representation. The study adopts the liberal feminism theory as its theoretical framework. The study employs qualitative research design in which primary data were collected using interview. Findings shows that the low representation of women in politics in Lagos state and Nigeria is linked with barriers and obstacles like Religion, education, financing, patriarchy, political violence, bullying, perception from other women. This study recommended establishment of mentorship groups, increment of women’s political education and empowerment, improve access to financial resources, introduction, and enforcement of affirmative actions as well as the encouragement of political parties to nominate women candidates for key positions.